Ubezpieczenia gospodarcze jako instrument zarządzania ryzykiem w rolnictwie. Doświadczenia wybranych państw Unii Europejskiej - Szymecka, Agnieszka (Wydawnictwo Naukowe UAM, 2008)
In the face of a growing agricultural production risk and related price increase, risk management in agriculture is becoming increasingly important. Higher price risk is a result of continuing reforms of the Common Agricultural Policy and the weakening of the existing risk management mechanisms. Increased agricultural production risk is caused by escalating occurrences of adverse weather conditions resulting from climatic changes, which consequently bring about frequent and growing losses in the process of agricultural production. Hence such an importance of risk management today. The paper focuses on the system of agricultural produce insurance, which is one of the key risk management mechanisms. Both, advantages and pitfalls of developing insurance markets have been presented. Solutions functioning in Spain and Italy have been analysed and on that basis the current situation in Poland was assessed and described. The weaknesses of the Polish system were depicted and some desired changes postulated.

La problemática concernente la gestione del rischio riveste sempre piü importanza dinnanzi all’aumento del rischio di mercato e del rischio di produzione, entrambi legati allo svolgimento dell’attivitá agricola. L’aumento del rischio di mercato é la conseguenza delle riforme della Política Agricola Comune e del sempre piü limitato ruolo dei finora vigenti strumenti preposti per la sua gestione. L’aumento del rischio di produzione invece é legato al crescente verificarsi di fenomeni atmosferici negativi - conseguenza dei cambiamenti climatici - che comportano sempre piü spesso e sempre piü grandi danni alle produzioni agricole. Sotto questo aspetto, la problemática degli strumenti di gestione del richio diventa molto attuale. L’oggetto dell’articolo é il sistema delle assicurazioni agricole come uno degli strumenti di base di gestione del rischio di produzione, individuandone i benefici e le difficoltá legate al loro sviluppo. L’ananlisi riguarda anche le soluzioni adottate in materia in Spagna e in Italia. Sulla base della predetta analisi sono state valutate le soluzioni vigenti in Polonia, con indicazione dei punti deboli e dei cambiamenti necessari.
Economic insurance as a risk management instrument in agriculture: experiences of selected EU member states
L'assicurazione come strumento dl gestione del rischio in agricoltura: esperienze di alcuni paesi dell'Unione Europea